Nanoscale Phenomena Basic Science to Device Applications - Tang, Zikang; Sheng, Ping.; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
Nanotechnology is the result of the continuing technological trend toward device miniaturization and the characterization, manipulation, and fine control of structure and function at diminishing length scales. A large class of nanoscale materials can be stable even though they are far from the lowest-energy thermodynamic state, and many possess novel properties unattainable in bulk. These trends are supported by the increasing sophistication of characterization and fabrication tools such as the scanning tunneling microscope and the transmission electron microscope, which allow the resolution and manipulation of single atoms and molecules. Nanoscale Phenomena: Basic Science to Device Applications presents selected lectures from the Third Workshop of the Croucher Advanced Study Institute on Nano Science and Technology, and showcases contributions from world-renowned researchers. Chapters fall into four major categories: Nanostructured Carbon and its Applications, Quantum Dots and Molecular Spintronics, Nanomaterials Design and Synthesis, and Molecular Electronics.
Nano Structured Carbons and their Applications -- Science and Technology of Nanocarbons -- Catalytically-Grown Carbon Nanotubes and Their Current Applications -- Transparent Conducting Films by Using Carbon Nanotubes -- Raman Spectroscopy on Double-Walled Carbon Nanotubes -- Interface Design of Carbon Nano-Materials for Energy Storage -- Formation Mechanism of 0.4,nm Single-Walled Carbon Nanotubes in CoAPO-5 Single Crystals -- Quantum Dots and Molecular Spintronics -- Nanodevices and Maxwell$1 (Bs Demon -- Manipulating Electron Spins in an InGaAs/InAlAs Two-Dimensional Electron Gas -- Continuum Modelling of Nanoscale Hydrodynamics -- Defect in Zinc Oxide Nanostructures Synthesized by a Hydrothermal Method -- Nano Materials Design and Synthesis -- Towards Surface Science Studies of Surfaces Formed by Molecular Assemblies Using Scanning Tunneling Microscopy -- Electronic Transport Through Metal Nanowire Contacts -- Synthesis and Properties of Quasi-One-Dimensional Nitride Nanostructures -- Electron Energy-Loss Spectroscopy for Nannomaterials -- Fabrication of Photovoltaic Devices by Layer-by-Layer Polyelectrolyte Deposition Method -- Optical Properties of Arrays of Iodine Molecular Chains Formed Inside the Channels of AlPO4-5 Zeolite Crystals -- Molecular Electronics -- Quantum Manipulation at Molecule Scale -- Silicon-Based Nano Devices for Detection of DNA Molecules -- From Simple Molecules to Molecular Functional Materials and Nanoscience -- First-Principles Method for Open Electronic Systems.s
Keywords: Materials science; Biophysics; Biological physics; Electronics; Microelectronics; Optical materials; Electronic materials; Nanotechnology; Materials Science; Nanotechnology; Optical and Electronic Materials; Electronics and Microelectronics, Instrumentation; Characterization and Evaluation of Materials; Biophysics and Biological Physics; Electronic books